Financial development and human development in Nigeria - Afolabi Mutiu Adeniyi; Bosede Akanbi; Onifade Emmanuel Olayinka (REGION, 2023)
This study examines the relationship between financial development indicators and human development in Nigeria from 1990-2019. It investigates the effect of broad money supply/Gross Domestic Product (GDP) on Human development; it examines the impact of credit supply/GDP on human development and assesses the link between market capitalization and human development. The study employs expo-facto research design and Autoregressive Distributed Lag to examine the relationship between Financial Development and Human Development. Previous studies in Nigeria had focused on financial development and economic growth, financial deepening and economic growth. Therefore, this study is a response to the dearth of relevant empirical studies on financial development and human development in Nigeria. From the results, the long run net effect of broad money supply/GDP on human development is negligible and positive. M2/GDP in Nigeria only account for the extent of monetization rather than financial intermediation. The long run net effect of credit supply/GDP on human development is negligible and positive. The long-run effect of M2/GDP, CPS/GDP are statistically significant but has no power to substantially influence human development in Nigeria. The study suggests that banks should effectively perform their intermediation roles and effort should be made by the policy makers to widen/broaden the Nigeria capital market activity. Policy makers should concentrate on financial system and their roles for effective money supply and credit supply while implementing economic policies.
Keywords: E5; I00; O10; 330; Financial development; Human Development; M2; CPS; GDP; ARDL